International Monetary Fund Annual Report 1963. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1963)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1963. The report highlights that during the course of 1962, economic activity continued to expand in most industrial countries. In the United States, there was some slowdown in production, but final purchases rose almost as much as during 1961, and a revival of activity set in during the early part of 1963. In continental Europe, a climate of general prosperity continued to prevail.